Política criminal no estado social e democrático de eireito - Machado, Pedro Orestes de Oliveira (2024)
The research aims to conduct a comprehensive analysis on developing an effective criminal policy for Brazil, based on the principles of a social and democratic state under the rule of law, in response to the high crime rates that have plagued the country in recent decades. The growing social fear of violence in the streets reflects the urgent need to seek a future where Brazil is recognized as a safe place. However, the complexity of the criminal landscape, driven by constant changes in social relations due to globalization, and the inefficacy of the Brazilian penal system make this optimistic vision a challenging reality. The research adopts a multidisciplinary approach, using concepts from modern criminology and political theory, to identify strategies that go beyond simplistic and quick solutions. The proposed empirical and theoretical analysis aims to address the lack of scientific grounding in the formulation of Brazilian criminal policy, replacing it with strategies based on concrete data and respect for constitutional principles. The study also seeks to understand the role of imprisonment and the prison environment in combating crime, exploring their functions within a context of effectiveness and legitimacy. Through a comprehensive literature review and statistical data analysis, the research aims to outline the necessary guidelines for developing a more effective criminal policy in Brazil, aligned with penal principles and constitutional guarantees. By integrating theory and practice, this study seeks to contribute to the advancement of academic debate and the formulation of more effective public policies to address crime in the country